Adaptive mechanisms of cardiovascular system in trained athletes - Ilona Malinowska; Anna Maria Dobosiewicz; Łucja Stalmirska; Ewelina Pankanin (Kazimierz Wielki University, 2017)
Under the influence of training in the cardiovascular system, there are many changes. These morphological involve changes, metabolism and cardiac function. The team of these adaptations is called the "athlete's heart" when they appear as a physiological response is intense physical activity. However, there are also pathological changes be small that characterized by excessive hypertrophy and heart disorders in its function. The most important cardiac disturbances are sinus bradycardia, atrioventricular and intraventricular conduction disturbances, and changes in repolarization. Causes excessive cardiac hypertrophy of the fibrous rings of the valve apparatus to be stretched which results in valve regurgitation. There are no standards defining the boundary between physiological and pathological changes. The most frequent causes of sudden cardiac death among sporters are cardiac hypertrophic cardiomyopathy, coronary artery anomalies, cardiac arrest and other cardiovascular events.